Implication of Using Electronic Fiscal Devices on Audit Effectiveness among Small Business Owners of Arusha – Tanzania - Lubua, Edison Wazoel (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This study evaluated the use of Electronic Fiscal Devices among small business owners based in Arusha City Council – Tanzania. The focus was on the impact of the rate of using Electronic Fiscal Devices on the perceived effectiveness of the audit process. In addition, the study evaluated the impact of demographic variables, that is, the age of respondents, gender, level of education and business experience on the rate of using Electronic Fiscal Devices. Given the constant advocacy of the Tanzania Revenue Authority on the benefits of EFD uses in auditing, it was necessary to validate their assumptions based on the perception of users. In its approach, the study used mixed methods. The sample had 279 respondents. Data analysis was through descriptive and inferential statistics such as ordinal regression and the One-Way ANOVA. Results showed that the age, gender and business experience were not good determinants of the rate of EFD use. The level of education was a good determinant, but, with a reversal impact. Also, the rate of EFD uses among small business owners did not showed its perceived impact on the audit effectiveness. The study concludes that the observed reversal impact of education is a sign that people with a good level of education, may be using their knowledge to facilitate tax evasion. In addition, it concludes that factors other than the rate of EFD use are important to enhance the perception of small business owners on audit effectiveness. The study recommends the increase of EFD use advocacy by the revenue authority. Also, it recommends further studies to factors other than the rate of EFD uses, so as to determine the perception of taxpayers on audit effectiveness.